In prior's wood [large type] : a Max Tudor mystery - Malliet, G. M., 1951- (Malliet, G. M., 1951- Max Tudor novel., 2018)
Now Vicar of St. Edwold's in Nether Monkslip, former spy Max Tudor is working on a sermon about Bathsheba when news comes that Lady Duxter has been found in a suicide pact with her young lover. Lord Duxter rallies quickly - too quickly, it's murmured in the village. Having offered the manor house for a writers' retreat, he insists the show must go on. But when a young girl goes missing and a crime writer is targeted, DCI Cotton asks Max to lend his MI5 expertise.